Mediterranean Diet Patterns in Relation to Lung Cancer Risk: A Meta-Analysis - Du, Hongzhen; Cao, Tengrui; Lu, Xuning; Zhang, Tianfeng; Luo, Bin; Li, Zengning (Frontiers in Nutrition, 2022)
Background We systematically quantified the currently inconclusive association between Mediterranean diet patterns and the risk of lung cancer. Methods We searched the PubMed, Cochrane, Database of Abstracts of Reviews of Effects (DARE) and Web of Science electronic databases to identify relevant articles published before October 2021. We used the Newcastle–Ottawa scale to assess the quality of the published research and a random-effects model to estimate the aggregate hazard ratios and 95% CIs. As a result of significant heterogeneity, we performed subgroup analysis, meta-regression analysis, and sensitivity analysis. Where data were available, we also performed a dose–response analysis. Results Nine articles were included in the meta-analysis. The meta-analysis showed that there was a significant negative correlation between Mediterranean diet patterns and the risk of lung cancer in the general population with a hazard ratio of 0.82, a 95% CI of 0.74–0.92, and a high heterogeneity (I2 = 59.9%, P < 0.05). As a result of the significant heterogeneity, we conducted subgroup analysis, meta-regression analysis, and sensitivity analysis and found that the study design was the source of the heterogeneity. Subgroup analysis and sensitivity analysis showed that the final results did not change very much, the sensitivity was low and the results were relatively stable. The dose–response relationship showed that, based on the lowest Mediterranean diet score (0 points), for every three-point increase, the risk of lung cancer was reduced by 9%. Conclusion The evidence in this meta-analysis shows that there is a significant negative correlation between Mediterranean diet patterns and the risk of lung cancer, suggesting that Mediterranean diets are a protective factor in lung cancer.